2019
DOI: 10.1002/jbm.a.36741
|View full text |Cite
|
Sign up to set email alerts
|

Novel dual‐responsive semi‐interpenetrating polymer network hydrogels for controlled release of anticancer drugs

Abstract: Novel dual-responsive hydrogels of semi-interpenetrating polymer networks (semi-IPNs) based on temperature-sensitive N-isopropylacrylamide (NIPAA) and pH-sensitive Nethylmaleamic acid (NEMA) monomers and sodium alginate polymer were synthesized using free-radical polymerization in the presence of N,N 0 -methylenebisacrylamide as a crosslinker. Stimuli-responsive properties of the semi-IPN hydrogels showed remarkable sensitivity to both temperature and pH without limitation in NEMA content. Doxorubicin hydrochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Flow Cytometry Analysis and Immunohistochemistry. After 15 days of treatment, some mice were euthanized, and their tumor cells were collected by digesting the tumor in DMEM containing deoxyribonuclease (0.1 mg/mL) and collagenase (0.5 mg/ mL) for 60 min at 37 °C and agitation at 1200 rpm, and then stained with antibodies (CD3, CD4, CD8, CD206, F4/80, PD-L1, and FOXP3) in a flow type detection tube for 40 were also encased in paraffin and then sliced into 5 μm sections for analysis via immunohistochemistry (CD8, CD206).…”
Section: 7mentioning
confidence: 99%
“…Flow Cytometry Analysis and Immunohistochemistry. After 15 days of treatment, some mice were euthanized, and their tumor cells were collected by digesting the tumor in DMEM containing deoxyribonuclease (0.1 mg/mL) and collagenase (0.5 mg/ mL) for 60 min at 37 °C and agitation at 1200 rpm, and then stained with antibodies (CD3, CD4, CD8, CD206, F4/80, PD-L1, and FOXP3) in a flow type detection tube for 40 were also encased in paraffin and then sliced into 5 μm sections for analysis via immunohistochemistry (CD8, CD206).…”
Section: 7mentioning
confidence: 99%
“…Adequate research has shown that the IPN and SIPN structures can improve the mechanical performance and dimensional stability of functional hydrogels, [461,470,471] even the response rate of some stimuli-responsive hydrogels. [472,473] DN hydrogels DN hydrogels are special type of IPN hydrogels that possess two different types of network structures, the highly crosslinked polyelectrolyte network acts as the first network, which provides a rigid bracket for the DN, and the poorly crosslinked or non-crosslinked neutral network structure acts as the second network, fills in the rigid network to retain the gel shape and absorb external stress. [474][475][476] DN hydrogels are attracting increasing attention due to their excellent mechanical strength and other resulting in mechanical properties, [86,[476][477][478][479][480][481] and increasingly more uniquely structured DN hydrogels have been Figure 16.…”
Section: Figure 14 Schematic Illustrations Of An Sipn (A) and A Fipn (B)mentioning
confidence: 99%
“…Nowadays, stimuli-responsive polymers have received much attention for the development in the field of drug release via regulating their morphologies or aggregation properties. [1,2] However, the low drug loading strongly limits its application as organic carriers in drug delivery. [3] Thus, since Vallet-Regi and co-workers reported firstly application of mesoporous silica (MCM-41) for drug assembly and controlled release, [4] formulating a novel inorganic material with nanoporous features as a drug carrier may be one of the effective approaches to overcome this disadvantage.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, stimuli‐responsive polymers have received much attention for the development in the field of drug release via regulating their morphologies or aggregation properties . However, the low drug loading strongly limits its application as organic carriers in drug delivery .…”
Section: Introductionmentioning
confidence: 99%